ASME 2010 8th International Conference on Nanochannels, Microchannels, and Minichannels: Parts a and B 2010
DOI: 10.1115/fedsm-icnmm2010-30412
|View full text |Cite
|
Sign up to set email alerts
|

Optothermal Control of Local Fluid Temperature in Microfluidics

Abstract: This paper outlines an optothermal approach to manipulate local fluid temperatures in microfluidic and lab-on-chip systems. The system has the ability to control the size, location and the source heat flux using an external computer and is not constrained by predefined geometries, complex fabrication or control system. The thermal performance is evaluated using a temperature-dependent fluorescent dye. Experiments demonstrate localized heating up to 35°C over ambient temperature for a heat source spanning a dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Images were projected onto the surface of the black tape using the abovementioned optical setup controlled by a laptop. We performed in situ temperature field imaging based upon the temperature-dependent quantum efficiency of rhodamine B, using the method introduced by Ross and coworkers [22] and described in our previous work [21]. Briefly, 0.1 mM rhodamine B in 900 mM Tris-borate buffer solution was prepared and introduced into the microchannel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Images were projected onto the surface of the black tape using the abovementioned optical setup controlled by a laptop. We performed in situ temperature field imaging based upon the temperature-dependent quantum efficiency of rhodamine B, using the method introduced by Ross and coworkers [22] and described in our previous work [21]. Briefly, 0.1 mM rhodamine B in 900 mM Tris-borate buffer solution was prepared and introduced into the microchannel.…”
Section: Resultsmentioning
confidence: 99%
“…The corrected raw images were then normalized with the corrected cold field images. The intensity values of the treated images were then converted to temperature using the intensity vs. temperature calibration, as described by [21]. Figure 1 shows the Gaussian shape steady state temperature profile for no-flow condition along the microchannel produced by a heater size of approximately 1.5 , after taking cross-sectional averaging at each axial location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. The total measured pressure drop is a summation of different effects: ΔP total =ΔPnormalI+ΔP en +ΔP FD +ΔP minor +ΔP ev ,where ΔPnormalI is the pressure drop in the connecting, tube which was measured directly at each flow rate, ΔP en is the pressure drop in the inlet region, ΔP FD is the pressure drop in the fully developed region of the microchannel, ΔP minor is the pressure drop due to the bends in the microchannel inlet, and ΔP ev is the pressure drop due to the electroviscous effect .…”
Section: Experimental Validationmentioning
confidence: 99%
“…Akbari et al. showed that ΔP minor and ΔP ev are less than 1% of the pressure drop in the fully developed region, ΔP FD , and therefore they could be neglected. On this basis, the measured pressure drop in the microchannel was related to the pressure drop in the fully developed region of the microchannel once ΔPnormalI had been determined.…”
Section: Experimental Validationmentioning
confidence: 99%